2013
DOI: 10.1108/ccm-02-2012-0016
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of UK and Taiwanese chemical plant managers

Abstract: Purpose -The purpose of this paper is to compare the competencies of managers in the UK and Taiwan. Design/methodology/approach -A comparative analysis of managers using a behavioural event interviewing (BEI) technique. Findings -Both cultures were highly achievement focussed. However, there were several marked differences in other behaviours which appear to be cultural in nature. UK managers demonstrated more interpersonal awareness, and concern for impact, whereas Taiwanese managers were more likely to demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Research has demonstrated that management systems within global organizations do not perform similarly across different national contexts (Den Hartog and Verburg, 2004;DiMaggio and Powell, 1983;Lawrence and Lorsch, 1967;Soin and Scheytt, 2006;Vickers, 2013). Understanding the relationship between site-specific contextual and institutional factors that affect OP remains a formidable challenge for globally oriented academicians and practitioners (Weerakkody et al, 2009).…”
Section: Organizational Behavior Varies By Contextmentioning
confidence: 99%
“…Research has demonstrated that management systems within global organizations do not perform similarly across different national contexts (Den Hartog and Verburg, 2004;DiMaggio and Powell, 1983;Lawrence and Lorsch, 1967;Soin and Scheytt, 2006;Vickers, 2013). Understanding the relationship between site-specific contextual and institutional factors that affect OP remains a formidable challenge for globally oriented academicians and practitioners (Weerakkody et al, 2009).…”
Section: Organizational Behavior Varies By Contextmentioning
confidence: 99%
“…This review is based on "A comparative study of UK and Taiwanese chemical plant managers" by Vickers (2013). Using a behavioral event interviewing technique, he compares the competencies of managers in both countries who all work for the same organization.…”
Section: Commentmentioning
confidence: 99%